62.0k views
4 votes
Solve -11 - x + = - 5 (2x-3) + 7

User Lindstrom
by
6.0k points

1 Answer

0 votes

Answer:

Let's see what to do buddy...

Explanation:

_________________________________


- 11 - x = - 5(2x - 3) + 7


- 11 - x = - 10x + 15 + 7


- 11 - x = - 10x + 22

Subtract the sides of the equation plus 11 :


- x = - 10x + 22 + 11


- x = - 10x + 33

Subtract the sides of the equation plus 10x


10x - x = 10x - 10x + 33


9x = 33

Divided the sides of the equation by 9


(9)/(9)x = (33)/(9) \\


x = (33)/(9) = (3 * 11)/(3 * 3) = (11)/(3) \\

And we're done.

Thanks for watching buddy good luck.

♥️♥️♥️♥️♥️

User Rakesh B E
by
5.9k points